Comparison of the Effects of Electroacupuncture and Melatonin on Nerve Regeneration in Experimentally Nerve-Damaged Rats - Yasemin Özkan; Mehmet Turgut; Yasemin Turan; Mehmet Dinçer Bilgin; Sinem Sari; Mustafa Yilmaz; Yiğit Uyanikgil; Mahmut Alp Kiliç; Derya Tanriöver; Zehra Seznur Kasar (Medical Association of Pharmacopuncture Institute, 2021)
Background : Development of methods to accelerate nerve regeneration in peripheral nerve damage is important. Electroacupuncture is a new therapeutic method that combines traditional acupuncture with modern electrotherapy. Melatonin has been shown to reduce nerve damage. Objectives: In this study, we aimed to determine and compare the therapeutic effects of electroacupuncture and melatonin on rat sciatic nerve injury. Methods : A total of 56 adult male Wistar Albino rats were divided into four study groups with 14 animals in each group: intact control (group I), subcutaneous saline (group II), subcutaneous melatonin (group III), and electroacupuncture (group IV). Surgical procedure including unilateral (right) sciatic nerve injury was applied to groups II, III, and IV. Saline and melatonin started immediately after surgery for six weeks, while electroacupuncture was given two weeks after surgery for 3 weeks. Functional and histological assessments were used as outcome measurements. Results : Sciatic nerve damage caused a significant decrease in nerve conduction velocity. Both electroacupuncture treatment and melatonin treatment significantly increased the nerve conduction velocity. Both sciatic functional recovery and histological regeneration were faster in these treatment groups compared to the saline. However, no significant difference was observed between the two treatment groups. Conclusion : Electroacupuncture and melatonin are promising alternative treatment strategies for peripheral nerve damage and can be examined in detail in future studies.